Global burden of potentially life-threatening maternal conditions: a systematic review and meta-analysis - Fitiwi Tinsae Baykemagn; Girmatsion Fisseha Abreha; Yibrah Berhe Zelelow; Abadi Kidanemariam Berhe; Alemayehu Bayray Kahsay (BMC, 2024)
Abstract Background Potentially life-threatening maternal conditions (PLTCs) is an important proxy indicator of maternal mortality and the quality of maternal health services. It is helpful to monitor the rates of severe maternal morbidity to evaluate the quality of maternal care, particularly in low- and lower-middle-income countries. This study aims to systematically identify and synthesize available evidence on PLTCs. Methods We searched studies in English from 2009‒2023 in PubMed, the National Library of Medicine (NLM) Gateway, the POPLINE database, and the Science Direct website. The study team independently reviewed the illegibility criteria of the articles. Two reviewers independently appraised the included articles using the Joanna Briggs Instrument for observational studies. Disputes between the reviewers were resolved by consensus with a third reviewer. Meta-analysis was conducted in Stata version 16. The pooled proportion of PLTCs was calculated using the random effects model. The heterogeneity test was performed using the Cochrane Q test, and its level was determined using the I2 statistical result. Using Egger's test, the publication bias was assessed. Result Thirty-two cross-sectional, five case-control, and seven cohort studies published from 2009 to 2023 were included in the meta-analysis. The highest proportion of PLTC was 17.55% (95% CI: 15.51, 19.79) in Ethiopia, and the lowest was 0.83% (95% CI: 0.73, 0.95) in Iraq. The pooled proportion of PLTC was 6.98% (95% CI: 5.98-7.98). In the subgroup analysis, the pooled prevalence varied based on country income level: in low-income 13.44% (95% CI: 11.88-15.00) I2 = 89.90%, low-middle income 7.42% (95% CI: 5.99-8.86) I2 = 99.71%, upper-middle income 6.35% (95% CI: 4.21-8.50) I2 = 99.92%, and high-income 2.67% (95% CI: 2.34-2.99) I2 = 99.57%. Similarly, it varied based on the diagnosis criteria; WHO diagnosis criteria used 7.77% (95% CI: 6.10-9.44) I2 = 99.96% at P = 0.00, while the Centers for Disease Controls (CDC) diagnosis criteria used 2.19% (95% CI: 1.89-2.50) I2 = 99.41% at P = 0.00. Conclusion The pooled prevalence of PLTC is high globally, predominantly in low-income countries. The large disparity of potentially life-threatening conditions among different areas needs targeted intervention, particularly for women residing in low-income countries. The WHO diagnosis criteria minimize the underreporting of severe maternal morbidity. Trial registration CRD42023409229.